Propuesta de un plan estratégico para la empresa PC soluciones de la ciudad de Loja periodo 2015 -2019 - Valdivieso Alejandro, Byron Alexander (2016)
Today companies are barriers that do not allow their expansion and growth in the market, this forces implement strategic plans that help develop internally and that is where we should analyze the importance of proper strategic planning because today subsistence competition and market focus on: customer satisfaction, grab greater percentage of them and provide quality services. This research raises the overall objective of "PROPOSAL FOR A STRATEGIC PLAN FOR THE COMPANY PC SOLUTIONS OF THE CITY OF LOJA PERIOD 2015 - 2019" it will allow long term, achieve better development and performance of its activities, with a view to get better results in their daily work and achieve a better positioning in the local market. This study corresponding conceptual elements considered most important and constitute the bibliographic database of issues of strategic planning for the development of this research. Within the methods and techniques used consists descriptive, analytical, deductive and inductive method; which served to prepare and develop the project objectives and the same techniques were applied as direct observation, interview (manager), surveys (5 employees and 249 customers) that provided for the primary information needed to clarify the current situation the company. a situational diagnosis of the company, in the external analysis, table of evaluation of external factors, the sum of total weighted between opportunities and threats was made, gives a value of 2.66 points; which means that this on acceptable average of the factors, which conclude by saying that in this case the opportunities are greater threats; and therefore is defined in the external environment is no more consistent opportunities than threats and that the company should take advantage of the best way these factors are favorable for its development and internal analysis with the EFI matrix, internal factors, the sum of total weighted between the strengths and weaknesses gives a value of 2.50 points; representing that the company has many weaknesses, it must be taken into account because it needs the increase strengths within it. Among the strategic objectives set five objectives were identified: Improve business enterprise image Pc Solutions. Improving knowledge, skills and qualities and encourage the human talent of the company. widely advertise the products and services offered by the company. Increase the number of customers of the company. Improve the performance of each employee of the company. The strategic plan to be implemented amounts to a total of $ 7530.00 US dollars. Implement this strategic plan will allow the company to achieve a better development and positioning in the market selling products and provision of IT services, attracting clientele. Finally, conclusions and recommendations put forward for consideration the management of the company for later execution are presented.